(3YbO GdGjLGQ GdJehjdi (B/ s - (3eMehO eUWai YHOGddg s; (3SYjO SdjeGf LHQs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2012)
(3GdJCLjQ GdJehjdi hSjdI ef hSGFd GdeTQhYGJ MjK JdLG GdGTNGU GdWHjYjI hGdGYJHGQjI dTQcGJ GdJGNjQ GdJehjdi dci JTJQi dge GdGUhd GdQGSeGdjI HGdehGUaGJ GddGReI deHGTQI fTGWge GPG de Jcf JeJdcgG Ke Jbhe HJGLjQgG dge deOI RefjI eMOOI ebGHd bjeI GjLGQjI TgQjI jdRe GdeTQhY HSOGOgG WjdI eOI YbO GdGjLGQ GdJehjdi hai fgGjI GdeOI jMb ddeSJGLQ GdGNJjGQ Hjf KdGK GNJjGQGJ GeG GNJjGQ TQGA GdeGd GdeDLQ cdg Gh HYVIhGeG GNJjGQ JLOjO eOI YbO GdGjLGQ GdJehjdis
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdeOfi, (B2012s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B: (3UaMI (B410-422s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdeOfjs; (3GdGjLGQ GdJehjdis; (3GdJCLjQ GdJehjdis; (3YbO GdGjLGQ GdJehjdis; (3GdeTQhY GdeSJajOs; (3eRGjG GdJCLjQ GdJehjdj s; (3VeGfGJ s; (3GdJRGeGJs; (3JfGRds; (3GfbVGAs; (3YbO GdEjLGQ GdJehjdj hGdhYO HGdHjY s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdeOfjs